Comprehensive genome analysis of two novel Saccharopolyspora strains—Saccharopolyspora montiporae sp. nov. and Saccharopolyspora galaxeae sp. nov. isolated from stony corals in Hainan - Xie, Yuhui; Li, Fenfa; Xie, Qingyi; Kong, Fandong; Xu, Yun; Ma, Qingyun; Wu, Wenqiang; Huang, Dongyi; Xie, Xinqiang; Zhou, Shuangqing; Zhao, Youxing; Huang, Xiaolong (Frontiers in Microbiology, 2024)
Marine actinomycetes exhibit a high level of biodiversity and possess significant potential for the production of high-value secondary metabolites. During the course of investigation of marine actinobacteria from corals, two Saccharopolyspora strains, namely, HNM0983T and HNM0986T, were isolated from stony corals collected from the coastal area of Hainan Island. The 16S ribosomal RNA (rRNA) gene sequence analysis revealed that these two strains are putative novel taxa of the genus Saccharopolyspora. Whole-genome sequencing comparisons further confirmed the two strains as belonging to two novel Saccharopolyspora species, which can be distinguished phenotypically and chemically from their current closest phylogenetic relatives. Some genomic information of the genus Saccharopolyspora was compared for evaluating the production capacity of secondary metabolites. A total of 519 biosynthetic gene clusters (BGCs) from the genus Saccharopolyspora were used for analysis, and terpene BGCs were found to be widespread and most abundant in this genus. In addition, abundant novel BGCs in the genus Saccharopolyspora are not clustered with the known BGCs in the database, indicating that the metabolites of the genus Saccharopolyspora deserve further exploration. On the basis of these presented results, Saccharopolyspora montiporae sp. nov. (type strain = HNM0983T = CCTCC AA 2020014T = KCTC 49526T) and Saccharopolyspora galaxeae sp. nov. (type strain = HNM0986T = CCTCC AA 2020011T = KCTC 49524T) are proposed as the names for the new strains, respectively.